Assessment of reproductive and growth performance of pigs on commercial swine farms in southern Kyushu, Japan. (12th December 2020) - Sasaki, Yosuke; Kawabata, Tadahiro; Nakatake, Shingo; Kohigashi, Tomoya; Toya, Ryohei; Uemura, Ryoko; Sueyoshi, Masuo
Abstract: The objective of the present study was to assess the productivity of pigs to investigate the time‐dependent change in productivity and compare productivity according to breeding company group and porcine reproductive and respiratory syndrome (PRRS) status on commercial swine farms in southern Kyushu, Japan. Data used in the present study were 245 annual productivity records from 2014 to 2018 obtained from 72 farms. Average sow inventory was 481.2 sows. Mean numbers of pigs weaned per sow per year and market pigs sold per sow per year were 23.7 and 21.6, respectively. Pigs born alive per litter increased from 11.1 to 11.9 pigs from 2014 to 2018 ( p < .05). Farms using domestic breeding companies had similar numbers in 2016 to those using international breeding companies, but fewer pigs in 2014, 2015, 2017, and 2018 ( p < .05). Farms with an unknown or unstable PRRS status had fewer pigs born alive per litter and pigs weaned per sow per year than those with stable or negative PRRS statuses (11.2 ± 0.06 vs. 11.8 ± 0.08 pigs and 22.6 ± 0.38 vs. 25.0 ± 0.22 pigs, respectively; p < .05). These results can be used to establish feasible targets and standards of performance to identify problem areas and improve production.